DOI: 10.17077/etd.hxqics0u
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of student perceptions of autonomy, student-instructor dialogue and satisfaction in a web-based distance Russian language classroom

Abstract: The purpose of this mixed methods study was to explore the relationship between autonomy, student-instructor dialogue, and student satisfaction within a web-based distance Russian language course. Forty six (46) students from two US higher education institutions participated in this study. Using an Exploratory Model with the elements of an Explanatory Model (Creswell & Plano Clark, 2007), the qualitative and quantitative data were collected at the middle and at the end of the course to provide thorough investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 116 publications
1
7
0
2
Order By: Relevance
“…Finally, the finding of the study to some extent is consistent with that of Kostina (2011) which revealed that autonomy, dialogue and satisfaction have significant correlation at the beginning and the middle point of the course. However, the relationship among them significantly decreased towards the end of the course.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, the finding of the study to some extent is consistent with that of Kostina (2011) which revealed that autonomy, dialogue and satisfaction have significant correlation at the beginning and the middle point of the course. However, the relationship among them significantly decreased towards the end of the course.…”
Section: Discussionsupporting
confidence: 88%
“…This study contributes to local literature on how tutoring support relates to retention of distance students at the University of Cape Coast on the premise of Moore's theory on 'Transactional distance' (with reference to dialogue). Kostina (2011) explored the relationship between autonomy, student-tutor dialogue and satisfaction at a Russian language web-based and found that, autonomy, dialogue and satisfaction had significant correlation at the beginning and the middle point of the course. However, the relationship among them significantly decreased towards the end of the course.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mirroring the findings of Archambault & Crippen (2009) and Dawley et al (2010), more than half (59.8%) of respondents have only been teaching online for five or fewer years. This indicates, as previous studies have suggested, online teaching has only recently begun to move into the area of language education (Kostina, 2011) where continued yearly increases in enrollments of online courses (Allen & Seaman, 2015Allen et al, 2016;National Center for Education Statistics, 2014;Snyder et al, 2016) is leading to a high demand for world languages (Gemin & Pape, 2017). As the field of OLE progresses, it is likely this number will change as the current online language teachers continue to gain experience in OLE.…”
Section: Population Of Online Language Teachersmentioning
confidence: 89%
“…For language learning, additional benefits that have been shown for online language learning than those previously mentioned for online instruction include: a platform for community language learning (Bailey & Hendricks, 2014;Kraemer, 2008), ready and easier access to authentic materials including audio and visual aids (Kostina, 2011), a way for individuals to stay connected to a language even when they are not close to other speakers (Bischoff, Bisconer, Kooker, & Woods, 1996), the potential to reach a higher proficiency in the target language (Blake, 2011) and the ability to offer a wider variety of languages (Lai et al, 2008). Thus, we live in a world where language learning no longer needs to be limited based on geography, but we have tools that can connect individuals anywhere who want to learn and are able to gain access to these tools.…”
Section: Distance Education and Language Learningmentioning
confidence: 99%
See 1 more Smart Citation